Is it alright to mix Qualitative and Quantitative Methods? - Kaushik, Sonika (JOURNAL OF INDIAN EDUCATION, 2017)
The paper explores the various dimensions of the debate on the mixing of qualitative and quantitative methods. Broadly, the two positions involved in the debate are — mixing of qualitative and quantitative methods causes epistemological damage; the choice of the method and the epistemological position are not necessarily linked. The paper deconstructs the positions and argues that the choice of the method is essentially rooted in the epistemological stance of the researcher